The Measurement & Verification of Energy Conservation Measures at a Coal-fired Power Plant - Larmour, Richard (Energy Research Centre, 2022)
The aim of this dissertation was to use Measurement & Verification (M&V) to determine the improvements in net heat rate at a South African coal-fired power plant (CFPP) following an extensive refurbishment programme. The CFPP consisted of multiple subcritical pulverised fuel generating units and the refurbishment programme aimed to improve the overall net heat rate by 1%. The purpose of using M&V is isolate the performance changes attributable to specific energy conservation measures from those changes brought about by other factors, or that would have occurred anyway for other reasons. An extensive literature review was undertaken, firstly into M&V and secondly into CFPP design and performance. The conventionally accepted methods for determining plant performance are the ‘direct method’ in which a measurement boundary is drawn around the entire plant, and the ‘components method’ which evaluates the boiler, the turbine-condenser cycle and the auxiliary loads separately. Caution is drawn to the fact that plant performance may be expressed in many ways depending on how HR is defined and on which coal measurement base is used. The physical factors affecting plant performance were classified as either fixed or variable. Fixed factors included vintage and design, size, condition of the major components (boiler, turbine and condenser), cooling water system type and pollutant controls. Variable factors included ambient conditions, flexibility of operations (such as running at part-load and load cycling) and the characteristics of the coal used including heating value, total moisture, hydrogen, ash, volatile matter, sulphur, hardness & abrasiveness. It is clear from the literature that the language used to describe flexible operations is inadequate and poorly defined. Other factors that may affect the calculated heat rate of a plant include coal weighing, stockpile surveys, length of assessment periods, changes to static stockpiles, measurement boundary selection and other assumptions. The literature review was used as a basis to develop an M&V methodology for the specific CFPP involved in the case study. The energy conservation measures were described in detail as well as constraints regarding availability and resolution of plant data. Although all measurement boundary options were considered, the whole facility approach was chosen (Option C). This approach was mainly motivated by the lack of data available and a high potential for interactive effects. Another reason is the fact that assessments need to capture the overall performance which could include deterioration in one part of the plant and simultaneous upgrades in other parts. The primary data required to find heat rate is the electrical energy use (exported, imported and auxiliary), the mass of coal consumed and the coal higher heating value. The M&V methodology included the development of a baseline adjustment model to adjust for changes in plant load, coal moisture and coal ash content. Ideally the model should have included changes in ambient conditions (temperature and relative humidity) but this was not possible as no ambient data was available and the assessment was done retrospectively. The absence of ambient data was mitigated by stipulating that assessment periods need to consist of a minimum of twelve consecutive months to account for changes in performance due to seasonal effects. The methodology also included a Monte Carlo analysis to quantify the combined uncertainties associated with electrical energy use, coal energy use, coal heating value and the adjustment model itself. The methodology was used to assess the change in net heat rate of the plant used in the case study for two separate twelve month reporting periods. The calculated impacts of the energy conservation measures were not as favourable as originally anticipated. A brief analysis of the results is provided with a discussion of potential reasons for the underperformance. A whole facility approach does not allow the reasons for performance changes to be pinpointed. One possibility is simply that the energy conservation measures had not been implemented as originally planned. An important finding was that the performance changes could not be solely attributed to the exclusion of any independent variables from the baseline adjustment model (e.g. ambient conditions). A more general discussion of the merits, shortcomings and limitations of the methodology is provided as well as some comments on the general interpretation of results. The baseline adjustment model is only applicable to the plant in the case study and is only valid for small changes in the independent variables. When calculating part-load operation, special attention must be given to generating units that have been derated. The application of a single part-load adjustment model to a multi-unit plant is discussed and found to result in conservative reporting. Factors which contribute to uncertainty, but which are unknown include staithe coal level changes, unknown stockpile dynamics, uncalibrated instruments, unrecorded coal movements and inaccuracy of aerial stockpile surveys. The dissertation concludes that the original hypothesis is supported: that a credible M&V methodology may be developed and applied to determine the heat rate improvements resulting from the refurbishment programme at a coal-fired power plant. Recommendations include an upfront agreement on which measurement reporting bases to use (both for heat rate and for coal), selection of a whole facility measurement boundary, a minimum assessment period of twelve months, installation of at least one accurate instrument to measure actual coal consumption (as opposed to coal delivered to the plant and then moved within the plant), sampling of coal, determination of heating value and collection of accurate ambient condition data from the start of the baseline period. Further recommendations are made to reduce uncertainty, determine static factors and to better interpret reported impacts.